Corrective Feedback in the Modern Language Classroom - Egan, Eithne (Trinity College Dublin, School of Education, 2017)
The research conducted in dissertation was carried out in the domain of second language acquisition in the modern foreign language classroom. Within the context of second language acquisition, this dissertation examined the use of corrective feedback in the language classroom and the potential effects it could have on the learning of modern foreign language students. Corrective feedback refers to a response given to an error that has been made by learners of a second language (Bitchener & Storch, 2016). Errors in language production by the learner can be responded to using both written or oral corrective feedback methods, depending on the type of error made and how it was produced i.e. in written text or verbally spoken.The aim of this thesis is to better understand the role a language instructor’s feedback can play in a student’s language learning. This study conducted desk-based research into this topic. This desk-based research consisted of a systematic literature review of studies in the last ten years, which investigated the use and possible effectiveness of corrective feedback on a learner’s language acquisition. Having collated the relevant studies to conduct this research, a thematic analysis of the literature was carried out to identify and more concisely understand the key themes and trends present in studies investigating second language acquisition and the effects of corrective feedback in this field. In relation to the contribution of knowledge to the topic of modern foreign language and corrective feedback, this dissertation provided an overview of the literature relating to the process of second language learning and situating the concept of corrective feedback within this field of education. In addition, this dissertation identified and analysed the most up-to-date studies in this research area. The key findings and conclusions drawn in these papers were considered against the current study’s research questions on whether corrective feedback is beneficial for language learning and what types of corrective feedback are most effective for second language acquisition. The results of this dissertation indicate that although there is some disagreement among researchers, generally speaking, corrective feedback is more advantageous for second language acquisition than receiving no corrective feedback. This dissertation also found that while, amongst researchers, there is no universally accepted most effective types of corrective feedback, the results indicate that indirect corrective feedback can facilitate more long-term and meaningful second language acquisition. Indirect corrective feedback refers to the indication that an erroneous utterance or production had occurred, whereas direct feedback identifies both the error and the target form (Bitchener, Young, & Cameron, 2005). Finally, as regards students experiencing a more profound and meaningful language learning, having received corrective feedback, the findings of this thesis suggest that language instructors should consider the age, proficiency levels, cultural background of students and their individual engagement with corrective feedback, as it was found that these factors can impact the way in which students perceive corrective feedback. It could be concluded that language instructors and policy makers should endeavour to provide their learners with the skills to engage with corrective feedback to enable them to become more autonomous language learners.
Keywords: Language learning; Corrective feedback; Second language acquisition